You are on page 1of 11

1

CHAPTER 3
EXPONENTS & RADICALS

3.1. Exponents

Exponents are also called powers or indices say how many times to use a
number in multiplication. It is also shorthand for repeated multiplication of the
same thing by itself. Similarly, it stands for how many times the number is
being multiplied by itself.
Let a e 9 and n
+
eZ
n
a (read as “a raised to the n or the nth power of a”) =
    

factors n
a a a a · · · ·
where a is the base and n is the exponent.
Illustrative Examples:
64 4 4 4 4
3
= · · = ( ) 64 4 4 4 4
3
÷ = · · ÷ = ÷ ( ) ( )( )( ) 64 4 4 4 4
3
÷ = ÷ ÷ ÷ = ÷
81 3 3 3 3 3
4
= · · · = ( ) 81 3 3 3 3 3
4
÷ = · · · ÷ = ÷ ( ) ( )( )( )( ) 81 3 3 3 3 3
4
= ÷ ÷ ÷ ÷ = ÷

3.2. Laws of Exponents
Let a, b e 9 and m, n
+
eZ
Laws of Exponents Illustrative Examples
1.
n m n m
a a a
+
= -
8 5 3 5 3
x x x x = = ·
+

( )( ) ( ) ( )
3 9 6 2 1 6 3 2 4 2 6 2 3 4
z y x 10 z y x 5 2 z y x 5 z y x 2 = · =
+ + +

2. ( )
mn n m
a a =
( )
( ) 15 5 3
5
3
y y y = =
( )
( ) y 12 6 y 2
6
y 2
x x x = =
3. ( )
m m m
b a ab =
( )
( ) 6 3 3 2 3
3
2
y x y x xy = =
( )
( ) ( ) ( ) 6 18 6 3 2 3 6 3 2 3
3
2 6 2
z y x 125 z y x 5 z y x 5 = =
4. 0 b ,
b
a
b
a
m
m
m
= = |
.
|

\
|

3
3
3
y
x
y
x
=
|
|
.
|

\
|
;
( ) ( )
( ) 8
12 8
4 2 4
4 3 4 2 4
4
2
3 2
z 81
y x 16
z 3
y x 2
z 3
y x 2
= =
|
|
.
|

\
|

5.
¦
¦
¹
¦
¦
´
¦
=
<
>
=
÷
÷
n m if , 1
n m if ,
a
1
n m if , a
a
a
m n
n m
n
m

4 2 6
2
6
x x
x
x
= =
÷
;
4 2 6 6
2
x
1
x
1
x
x
= =
÷
; 1
x
x
6
6
=
( )
( )
z y
x 8
z y
x 2
z y x w 2
z y x w 2
z y x w 4
z y wx 2
3
14
3
14 3
10 15 4 3
6
2
9 12 18 3 15
10 15 4 3 6
3
3 4 6 5
= = =

2

3.3. Multiplication of Polynomials

To multiply two polynomials, use the distributive law or multiply each term
of one of the polynomials by each term of the other, apply the laws of
exponents in multiplication and combine similar terms whenever necessary.

Illustrative Examples:
( ) ( ) ( )( ) ( )( ) y x 2 y x 3 y x 5 y x 3 xy 6 y x 3 y x 2 y x 5 xy 6 y x 3
5 3 2 5 2 3 2 4 3 2 5 5 2 4 3 2
÷ ÷ ÷ + ÷ = ÷ + ÷
=
4 7 8 4 7 3
y x 6 y x 15 y x 18 + ÷ ÷


( )( )
2 2
b ab ab a b b b a b a a a b a b a ÷ ÷ + = · ÷ · ÷ · + · = + ÷ =
2 2
b a ÷


( ) ( )( ) b b b a b a a a b a b a b a
2
· + · + · + · = + + = + =
2 2
b ab ab a + + +
=
2 2
b ab 2 a + +


( )( ) 7 x 5 x 2 x 3 7 x 2
2 3
÷ + ÷ + = ( )( ) ( )( ) ( )( ) ( )( ) 7 x 2 x 5 x 2 x 2 x 2 x 3 x 2
2 3
÷ + ÷
( ) ( ) ( ) ( ) 7 7 x 5 7 x 2 7 x 3 7
2 3
÷ + ÷ +
= 49 x 35 x 14 x 21 x 14 x 10 x 4 x 6
2 3 2 3 4
÷ + ÷ + ÷ + ÷
=
49 x 21 x 4 x 17 x 6
2 3 4
÷ + ÷ +


( )( )
2 2
y 16 xy 12 x 9 y 4 x 3 ÷ + ÷ = ( )( ) ( )( ) ( )( )
2 2
y 16 x 3 xy 12 x 3 x 9 x 3 ÷ +
( )( ) ( )( ) ( )( )
2 2
y 16 y 4 xy 12 y 4 x 9 y 4 ÷ ÷ ÷ + ÷ +
=
3 2 2 2 2 3
y 64 xy 48 y x 36 xy 48 y x 36 x 27 + ÷ ÷ ÷ +
=
3 2 3
y 64 xy 96 x 27 + ÷


Alternative Solution: Multiply vertically as shown below
49 x 21 x 4 x 17 x 6
49 x 35 x 14 x 21
x 14 x 10 x 4 x 6
7 x 2
7 x 5 x 2 x 3
2 3 4
2 3
2 3 4
2 3
÷ + ÷ +
÷ + ÷
÷ + ÷
+
÷ + ÷

3 2 3
3 2 2
2 2 3
2 2
y 64 xy 96 x 27
y 64 xy 48 y x 36
xy 48 y x 36 x 27
y 4 x 3
y 16 xy 12 x 9
+ ÷
+ ÷ ÷
÷ +
÷
÷ +


3
3.4. Division of Polynomials
Rule: To divide a monomial by a monomial, use the laws of exponents in division
Illustrative Example:
3
2 3
7
5
4
7
3 7 4
2 3 5 7
e
d
c
c
b
b
a
a
24
8
ce b a 24
d c b a 8
· · · ·
÷
=
÷
=
3 2
2 2 3
e b 3
d c a
÷

Rule: To divide a polynomial by a monomial, divide each term of the
polynomial by the given monomial.
Illustrative Example:
2 2
2
2
3 4
2
5
2
2 3
2
2 3 4 5 2 3
ab 4
b 16
ab 4
ab 12
ab 4
b a 40
ab 4
ab 36
ab 4
b a 24
ab 4
b 16 ab 12 b a 40 ab 36 b a 24
÷
+
÷
+
÷
÷
÷
÷
÷
=
÷
+ + ÷ ÷

=
ab
4
3 b a 10 b 9 a 6
3 3 2
÷ ÷ + + ÷

Rule: To divide a polynomial by another polynomial with atleast two terms:
1. Arrange the terms of both the dividend and the divisor in ascending or
descending powers of the variable.
2. Divide the first term of the dividend by the first term of the divisor
resulting the first term of the quotient.
3. Multiply each term of the divisor by the first term of the quotient, and
subtract the product from the dividend.
4. Use the difference or remainder obtained in step 3 as the new
dividend, and repeat steps 2 & 3.
5. Continue the process until the remainder is zero or a polynomial whose
degree is less than the degree of the divisor.
a. If the remainder is zero,
Quotient
Divisor
Dividend
=
.
b. If the remainder is not equal to zero,
Divisor
mainder Re
Quotient
Divisor
Dividend
+ =

Note: This rule is applicable only when the degree of the polynomial in
the numerator is greater than or equal to the degree of the
polynomial in the denominator.
4
Illustrative Examples:
1. ( ) ( ) 3 x 24 x 19 x 6 x 16 x 2 x 3
2 3 4 5
+ ÷ + ÷ + ÷ + =
8 x 9 x 5 x 7 x 3
2 3 4
+ ÷ + ÷

2.
7 x 2
49 x 21 x 4 x 17 x 6
2 3 4
+
÷ + ÷ +
=
7 x 5 x 2 x 3
2 3
÷ + ÷

Solutions:
8 x 9 x 5 x 7 x 3
0
24 x 8
24 x 8
x 27 x 9
x 19 x 9
x 15 x 5
x 6 x 5
x 21 x 7
x 16 x 7
x 9 x 3
24 x 19 x 6 x 16 x 2 x 3 3 x
2 3 4
2
2
2 3
2 3
3 4
3 4
4 5
2 3 4 5
+ ÷ + ÷
+ ÷
+
÷ ÷ ÷
÷ ÷
+ ÷
+
÷ ÷ ÷
÷ ÷
+ ÷
+ ÷ + ÷ + +

3.
5 x 6 x 2
8 x 47 x 83 x 55 x 6
2
2 3 5
÷ +
+ ÷ + ÷
=
5 x 6 x 2
2
2 x 7 x 9 x 3
2
2 3
÷ +
÷ ÷ + ÷


Solution:
2 x 7 x 9 x 3
2
10 x 12 x 4
8 x 12 x 4
x 35 x 42 x 14
x 47 x 38 x 14
x 45 x 54 x 18
x 83 x 40 x 18
x 15 x 18 x 6
8 x 47 x 83 x 55 x 6 5 x 6 x 2
2 3
2
2
2 3
2 3
2 3 4
2 3 4
3 4 5
2 3 5 2
÷ + ÷
÷
+ ÷ ÷ ÷
+ ÷ ÷
÷ + ÷
÷ +
+ ÷ ÷ ÷
+ ÷ ÷
÷ + ÷
+ ÷ + ÷ ÷ +

7 x 5 x 2 x 3
0
49 x 14
49 x 14
x 35 x 10
x 21 x 10
x 14 x 4
x 4 x 4
x 21 x 6
49 x 21 x 4 x 17 x 6 7 x 2
2 3
2
2
2 3
2 3
3 4
2 3 4
÷ + ÷
÷ ÷ ÷
÷ ÷
+ ÷
+
÷ ÷ ÷
÷ ÷
+ ÷
÷ + ÷ + +

5
3.5. Synthetic Division
Synthetic division is another method in finding the quotient of a
polynomial when the divisor is of the form a x ± . It is a short and simple
procedure that requires addition and multiplication applied to the
coefficients (which is the opposite of long division that requires division and
subtraction).
Steps in using Synthetic Division
1. Arrange all the terms of the dividend in descending powers of the
variable.
2. Write the numerical coefficients of each term of the dividend in a row. If
there is a missing power, replace it with a zero coefficient.
3. Substitute the divisor r x÷ by r and the divisor r x+ by r ÷ as the constant
divisor.
4. Multiply the largest coefficient of the variable (written on the third row) by
the constant divisor. Place the product aligns to the coefficient of the
second largest power and add it to that coefficient. Multiply the sum by
the constant divisor and place it align the coefficient of the next largest
power. Continue this procedure until there is a product added to the last
term (constant).
5. The last row indicates the coefficient of the terms in the quotient starting
from left to right which is one degree less than that of the dividend while
the last number in the last row is called the remainder.
Illustrative Examples:
1. ( ) ( ) 3 x 24 x 19 x 6 x 16 x 2 x 3
2 3 4 5
+ ÷ + ÷ + ÷ + 2. ( ) ( ) 4 x 48 x 30 x 35 x 2
3 5
÷ ÷ + + ÷
Solution: Solution:
– 3 3 2 –16 6 –19 24 4 2 0 –35 0 30 48
–9 21 –15 27 –24 8 32 –12 –48 –72
3 –7 5 –9 8 0 2 8 –3 –12 –18 –24
Hence, the quotient is Hence, the quotient is

8 x 9 x 5 x 7 x 3
2 3 4
+ ÷ + ÷

4 x
24
18 x 12 x 3 x 8 x 2
2 3 4
÷
÷ ÷ ÷ ÷ +

6
3.6. Zero, Negative and Fractional Exponents
For every 0 a= ,
1 a
0
=
and
n
n
a
1
a =
÷

Proof:
1
a
a
a a
n
n
n n 0
= = =
÷
. Therefore, 1 a
0
= .

n n
0
n 0 n
a
1
a
a
a a = = =
÷ ÷
. Therefore,
n
n
a
1
a =
÷
.
Note: The laws of exponents are also valid if the exponents are real numbers.

Illustrative Examples:
1. ( ) 1 x 7
0
= ( ) 7 1 7 x 7
0
= = ( ) 1 x 7
0
= ÷ ( ) 7 1 7 x 7
0
÷ = ÷ = ÷
2. ( )
x 7
1
x 7
1
=
÷

x
7
x
1
7 x 7
1
= |
.
|

\
|
=
÷
( )
x 7
1
x 7
1
÷ = ÷
÷

x
7
x
1
7 x 7
1
÷ = |
.
|

\
|
÷ = ÷
÷

3.
2
1
2
15
15
1
15
3 5
15
1
5
1
3
1
5
1
3
1
5 3
5 3
1 1
1 1
= · =
÷
=
÷
·
=
÷
÷ ÷
÷ ÷

4. Divide
2
x by
6
x
Method 1:
4 2 6 6
2
x
1
x
1
x
x
= =
÷
Method 2:
4
4 6 2
6
2
x
1
x x
x
x
= = =
÷ ÷

5.
5
2
3
6
3
2
y
x
y
x
÷
|
|
.
|

\
|
÷
|
|
.
|

\
|
=
( )
( ) 8 3 8
3
10 18
15 12
10
15
18
12
y x
1
y
x
y
x
y
x
y
x
÷ = ÷ = ÷ =
÷
·
÷
÷ +
÷ +
÷
÷

6.
( )
9
27
3
27 9
3
9 3
3
3 6 13 10
3 13
6 10
x 64
y
4
y x
4
y x
4
y x
y 20x
y 5x
÷ = ÷ =
|
|
.
|

\
|
÷ =
|
|
.
|

\
|
÷ =
|
|
.
|

\
|
÷
÷ ÷ ÷ ÷ ÷
÷
3

7.
( )
( )
( )
4
1
2
1
2
1
8
1
8) (
2
3
2/3
3
2
3
2
=
÷
=
÷
=
÷
= ÷
÷

8.
( ) ( )
xy y x
x
y
y
x
x
y
y
x
3 2 2 / 3 2 / 1
2 / 3
2
3
2 / 1
4 / 1
6
8
2
2 / 3
4 / 1
= = · =
|
|
.
|

\
|
|
|
.
|

\
|
÷ ÷ ÷ ÷ ÷ ÷
÷
÷
÷
÷
÷
÷
÷

9. ( )( ) y x y y x y x x y x y x
2 / 1 2 / 1 2 / 1 2 / 1 2 / 1 2 / 1 2 / 1 2 / 1
÷ = ÷ + ÷ = ÷ +
7
3.7. Radicals

A radical is a quantity or algebraic expression expressed as a root of
another quantity or algebraic expression denoted by
n
a
read as “the nth root of a “
where: n Z e is the index or order of the radical
a is the radicand
is the radical sign or symbol
Note: If there is no index appears in the radical, the index is understood to
be 2 (2
nd
order).

Let m/n e Q and a
+
eZ , then
( )
m
n n m
n
m
a a a = =

Illustrative Examples:
a a
2
1
=
4 3
4
3
a a =
3 3
1
a 2 a 2 = ( ) ( )
5
6
6
5
a 2 a 2 =

3.8. Laws on Radicals
Let m, n
+
eZ and a, b,
n
a,
n
b 9 e

Laws on Radicals
Simplification
of Radicals
Illustrative Examples
1.

( ) a a
n
n
=

where a > 0

Proof:
( ) a a a
n
n
n
n
= =

( ) 7 7
4
4
= ( ) xy xy
5
5
÷ = ÷
( ) 4 4 16
2
= = ( ) 2 2 8
3
3 3
÷ = ÷ = ÷
2.

n n n
b a ab =

where a , b > 0

Proof:
( )
n
1
ab ab
n
=
n n
b a b a
n
1
n
1
= =
Removing of
Perfect nth
Powers
2 6 2 36 72 = =
xy 3 z xy 10 xy 3 z y x 100 z y x 300
3 2 6 4 2 6 5 3
= =
3 2 3 2 3 2 3 9 6 3 3 10 6 5
c a 3 c ab 3 c a 3 c b a 27 c b a 81 ÷ = ÷ = ÷
( )( )
4
2 4 2
4
2 2 2
4
2
4
8 4 2
4
10 5 2
xy 2 y x 15 xy 2 xy 3 xy 5
xy 2 y x 81 xy 5 y x 162 xy 5
= =
=

8

Laws on Radicals
Simplification
of Radicals
Illustrative Examples
3.

n
n
n
b
a
b
a
=

where a , b > 0

Proof:
n
1
n
1
n
1
b
a
b
a
b
a
n
= |
.
|

\
|
=
n
n
b
a
=
Rationalizing
the
denominator
of the
radicand
y
xy
y
y
y
x
y
x
= · =
y
xy
y
y
y
x
y
x
3
2
3
2
3
2
3
3
3 = · =
ab 3
abc 6 5
ab 3
ab 3
ab 3
c 2 5
ab 3
c 50
= · =
xyz 2
z y x a 20
z y x 2
z y x 2
z y x 2
a 5
z y x 8
a 5
5
4 3 2 3
5
4 3 2 2
5
4 3 2 2
5
2 3 3
5 3
5
2 3
3
÷ = · ÷ = ÷
b a
b ab 2 a
b a
b a
b a
b a
b a
b a
÷
+ +
=
+
+
·
÷
+
=
÷
+

4.
mn n m mn
a a a = =


Proof:
mn
1
m
1
n
1
a a a
m n
= |
.
|

\
|
=

mn
a =

Reducing
the index to
the lowest
order

3 3 6
3 9 9 = = xy 10 y x 100 y x 100
2 2
4
2 2
= =
( ) ( ) ( ) ( )
y
y x 2
y
y x 2
y
y x 32
y
y x 32
2
5
10
5
10
10
5
÷
=
÷
=
÷
=
÷

( )
( )
( )
( ) y 3 x 2
b a
y 3 x 2 4
b a
y 3 x 2 4
b ab 2 a
2
2
4
2
2 2
÷
÷
=
÷
÷
=
÷
+ ÷


ssssssssssssss
( )
( )
( )
( )( )
( ) y 3 x 2
y 3 x b a 2
y 3 x 2
y 3 x 2
y 3 x 2
b a
÷
÷ ÷
=
÷
÷
·
÷
÷
=

Note: Let a 9 e

¦
¹
¦
´
¦
=
odd is n if a
even is n if a
a
n n

Illustrative Examples:
2 2 16
4 4 4
= = ( ) 2 2 16
4
4
4
= ÷ = x x
6 6
= ( ) x x x
6
6
6 6
= ÷ =
3 3 27
3 3 3
= = ( ) 3 3 27
3
3
3
÷ = ÷ = ÷ x x
5 5
= x x
5 5
÷ = ÷





9
3.9. Addition and Subtraction of Radicals
Two or more radicals are similar if and only if they have the same
a) order or index
b) radicand
otherwise, they are dissimilar.
Rule: To add or subtract two or more radicals, express each radical to its
simplest form and combine similar radicals whenever necessary.
Illustrative Examples:
1. ( ) 7 4 7 6 3 1 7 6 7 3 7 = + ÷ = + ÷
2. ( ) 0 xy 0 xy 2 8 6 xy 2 xy 8 xy 6
3 3 3 3 3
= = ÷ + ÷ = ÷ + ÷
3. ( ) ( ) ( ) ( ) 3 49 3 100 3 25 3 9 147 300 75 27 + ÷ ÷ = + ÷ ÷
3 7 3 10 3 5 3 3 + ÷ ÷ =
3 5 ÷ =
4.
3 5 3 3
xy 72 x 5 y x xy 6 y x 18 y 7 xy 8 xy 3 + ÷ ÷
xy 2 y 36 x 5 xy y x xy 6 xy 2 x 9 y 7 xy 2 4 xy 3
2 4 2 2
· + · ÷ · ÷ · =
xy 2 y 6 x 5 xy xy xy 6 xy 2 x 3 y 7 xy 2 2 xy 3
2
· + · ÷ · ÷ · =
xy 2 xy 30 xy y x 6 xy 2 xy 21 xy 2 xy 6
3 2
+ ÷ ÷ =
xy y x 6 xy 2 xy 15
3 2
÷ =
5.
a
b
a b a 4 b a b a 2
2
2 4 6 6 2 3 3 3
÷ + +
a
b a
b a 4 a b a ab 2 b a
2
6 6 2 2 2 2
÷ + · + · =
a
a
a
b a
b a 2 a ab ab 2 ab
2
3 3
· ÷ + + =
a
a b a
ab 2 b a a ab ab 2 ab
2
2 2
÷ · + + =
a ab ab 2 ab a ab ab 2 ab ÷ + + = ab 2 ab 2 =

10
3.10. Multiplication and Division of Radicals

To multiply or divide radicals having
a) the same order or index, use the law of radicals and simplify by
removing the perfect nth powers (multiplication) or rationalizing the
denominator (division).
n n n
ab b a =

n
n
n
b
a
b
a
=


b) different order or index, express them as radicals of the same order or
index by transforming each radicals in fractional exponents and
simplify.

Illustrative Examples:
A. Multiply the following:
1. ( )( ) ( ) ( ) 105 21 13 84 3 35 21 15 21 28 7 12 3 7 7 3 3 5 7 4 ÷ + = ÷ ÷ + = + ÷
21 13 21+ ÷ =
2. ( )( ) ( ) ( ) ( ) ( ) 30 75 45 3 25 5 9 3 5 5 3 3 5 5 3 3 5 5 3
2 2
÷ = ÷ = ÷ = ÷ = ÷ +
3. 3 9 7 16 7 4 7 4 7 4
2
= = ÷ = ÷ = ÷ +
4. ( ) ( )
3 3
2 2
3 3
3 9 6 9 3 3 6 3 3 3 6 3 3 3 6 3 · ÷ · = ÷ = ÷ +
3 27 27 54
3 3
= = ÷ =
5. xyz 2 z y x 3 xyz 2 z y x 9 z y x 18 z y x 3 z y x 6
2 3 2 4 6 3 5 7 2 3 4 2 3
= · = =
6.
4 2 2 4 2 8 4 4 4 10 5 5 4 9 3 2 4 2 3
abc 3 abc 2 abc 3 c b a 16 c b a 48 c b a 8 c b a 6 = · = =

7.
6 6 5 3
32 2 2 2 2 2 2 2 2
6
5
6
2 3
3
1
2
1
3
1
2
1
= = = = = · = ·
+
+

8.
6 6 3 2 3
108 3 2 3 2 3 2 3 2
6
3
6
2
2
1
3
1
= · = · = · = ·


11
B. Divide the following:
1. 2 4
6
24
6
24
= = =
2.
5
9
25
81
5 5
27 3
5
27
5
3
27
5
5
3
= =
·
·
= · = ÷
3.
3 3
3
3
2
2 5
3
2
3
2 5
y x 2 y x 8
y x 2
y x 16
y x 2
y x 16
= = =
4.
xy 4
yz x 4
y x 4
y x 4
xy 4
z
xy 16
z
z 16
y x
3
2 2
3
2
3
2
3
2 2
3 2
3
2
2
3
2
2 1
= · = =
÷
÷ ÷

5.
d c
d cd 2 c
d c
d cd cd c
d c
d c
d c
d c
d c
d c
÷
+ +
=
÷
+ + +
=
+
+
·
÷
+
=
÷
+

6.
d c
d c
d c
d c
d c
d c
d c
d c
2 2
÷
÷
=
÷
÷
·
÷
+
=
÷
+


7. 1
36
36
6
36
6
36
6
36
4
4
4
2
4
1
2
1
4
1
= = = =

8.
3
648
3
3
3
2
3
2
3
2
3
2
3
2
6
6 4
6 4
6 2
6 3
6
2
3
3
6
2
6
3
3
1
2
1
= · = = = =